Male DCIS diagnosed after use of over-the-counter hormonal supplement. (2019) - Agbroko, S.O.; Rojas, K.E.; Manasseh, D.M.; Borgen, P.
Highlights: As illustrated in this case report, male ductal carcinoma in-situ is a rare disease, and treatment is not standardized. Hormone-containing male enhancement supplements are unregulated and available over-the-counter. Hormonal supplementation may be related to the development or worsening of rare cases of male breast cancer. Abstract: Introduction: Male breast cancer is a rare disease. Although epidemiologic and genetic factors are associated with male breast cancer, hormonal factors may also play a role. Case presentation: We report the case of a 39-year-old BRCA negative male patient taking a sexual performance enhancement supplement who presented with worsening asymmetric gynecomastia and unilateral spontaneous bloody nipple discharge and was found to have ductal carcinoma in-situ. Discussion: The altered cellular environment related to the hormone contents of the supplement coincided with the rapid worsening of his gynecomastia and may have played a role in the development of the ductal carcinoma in-situ, or growth of an existing focus. Conclusion: The use of hormonal male enhancement supplements can lead to higher levels of androgens in users. It is possible for this altered hormonal environment to cause the growth of tumor or promote the progression of an existing focus.